Analisa Penyerangan untuk Cyber Security Social Engineering - Zein, Afrizal (Teknik Informatika Universitas Pamulang, 2023)
In the increasingly advanced digital era, threats to cyber security are increasing. One frequently used attack technique is social engineering, which involves psychological and social manipulation of individuals to gain confidential information or access to computer sistems. To counter this threat, there needs to be an effective solution. This study presents a critical analysis of such measures and tools to better address these issues. To combat cybersecurity social engineering, organisations have policies in place. These policies are implemented through a sistematic approach to ensure the protection of sensitive information. After conducting a comprehensive evaluation of recent research studies on the subject, our examination revealed the need to offer. To ensure an understanding of social engineering risks and the optimal methods to deal with them, employee training is essential. To prevent falling victim to harmful schemes, it is important to take protective measures. These measures can include introducing awareness programmes, educating non-technical personnel, implementing new security networks, using specialised software, and enforcing security protocols. The issue of social engineering is a major threat that cannot be ignored. It is important to take this issue seriously and implement measures that can protect individuals and organisations.